2019
DOI: 10.4315/0362-028x.jfp-18-545
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Virulence Potential of the Genus Aeromonas Isolated from Wild Rainbow Trout (Oncorhynchus mykiss) in Mexico

Abstract: The members of the Aeromonas genus are important foodborne pathogens, with a worldwide distribution. Wild rainbow trout, from the national protected area Santuario del Agua State Park, Corral de Piedra, were analyzed. Species of Aeromonas were isolated from the trout, and their pathogenic potential was analyzed based on different pathogenicity and virulence factors. The isolates were identified as A. allosaccharophila (n = 15), A. sobria (n = 8), A. veronii (n = 3), A. rivipollensis (n = 2), A. piscicola (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…What is important, both the T3-and T6-secretion systems operate independently, which significantly affects the bacterial virulence mechanisms. Although various factors have been attributed to bacterial virulence, several others still remain to be discovered (Reynolds, 2009;Khajanchi et al, 2010;Rangel et al, 2019;Reyes-Rodriguez et al, 2019). Recently, a growing number of scientific reports have suggested that environmental factors have a significant impact on the evolution of new metabolic adaptations that may be associated with bacterial pathogenicity (Staib & Fuchs, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…What is important, both the T3-and T6-secretion systems operate independently, which significantly affects the bacterial virulence mechanisms. Although various factors have been attributed to bacterial virulence, several others still remain to be discovered (Reynolds, 2009;Khajanchi et al, 2010;Rangel et al, 2019;Reyes-Rodriguez et al, 2019). Recently, a growing number of scientific reports have suggested that environmental factors have a significant impact on the evolution of new metabolic adaptations that may be associated with bacterial pathogenicity (Staib & Fuchs, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have shown that the toxicity of T3SS causes mutations in both, the structural genes and effector proteins, thereby demonstrating that structural genes are necessary for the toxicity and virulence of Aeromonas species, such as A. salmonicida and A. veronii (Reyes-Rodriguez et al, 2019). Effector proteins secreted via the type III secretion system, such as the serine/threonine kinase (AopO), tyrosine phosphatase (AopH), and ADPribosylating toxin (AexT) have been extensively studied.…”
Section: T3ss Secretion System and Effector Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The T3SS system facilitates their translocation through the plasma membrane into the host cell or the secretion of pore-forming translocators that facilitate the transport of effector proteins [ 75 , 76 ], and many researchers have indicated its importance and contribution to the multifactorial pathogenicity of Aeromonas . It is worth emphasizing that protein effectors secreted by this system are usually critical for bacterial virulence, e.g., loss of T3SS is sufficient to render the bacteria completely avirulent [ 19 , 77 , 78 ]. AexT is one of the effectors secreted by T3SS causing a detrimental effect on the cytoskeleton of the cell and disrupting actin filaments in the host cells, which may result in progressive damage to protein components.…”
Section: Discussionmentioning
confidence: 99%
“…Aeromonas possess a number of virulence mechanisms that are contributed to the pathogenesis of infection [ 17 , 18 ]. The production of extracellularly secreted enzymes and effector proteins/toxins, such as hemolysins, cytotoxic enterotoxins, proteases, lipases, as well as adhesion molecules (i.e., pili and lateral flagella), capsules, and the ability to biofilms formation, are known to be critical virulence-associated factors in both initial stages and progression of disease [ 7 , 19 ]. As it is commonly known, they are assigned a significant role in the regulation of bacterial virulence and pathogenicity by participating in infecting the host tissues and manipulating the host’s innate and adaptive immune responses [ 20 ].…”
Section: Introductionmentioning
confidence: 99%